Acaricidal Effect of Spondias Mombin Leaf Extract On Rhipicephalus (Boophilus) Microplus Female Tick - Adefila, Esther; Idowu, S. O.; Ademola, I. O.; Ayodele, E. O.; Odeniran, P. O. (Journal of Science, Technology and Innovation Research, 2026)
The leaf extract of Spondias mombin has demonstrated anthelmlinitc activity against gastrointestinal nematodes in sheep and adult Haemonchus placei. The active ingredients are molecules that are structurally related to Haem and are hypothesized to function by biological antagonism of haem uptake. Considering that several ectoparasites of livestock are blood sucking, we hypothesised that their survival could be dependent on haem-uptake, The experiments were performed using the adult immersion test (AIT), larval immersion test (LIT) and egg hatchability test (EHT) in 1.25% Triton X-100. For the AIT, the number of females laying eggs were recorded and placed in petri dishes, the petri dishes was incubated at 27–28ºC, 70–80% relative humidity, after 14 days, the eggs were collected, weighed and observed. Each treatment was incubated in replicate with standard drug solutions of cypermethrin using seven different dilutions. The AIT - response data fitted a sigmoidal equation well, (R2= 0.92, Sy.x = 7.90) with an EC50 value of 2.30mg/ml at 95 % confidence interval while Cypermethrin, gave an R2 value of 0.88, Sy.x = 11.00 with an EC50 value of 0.58mg/ml at 95 % confidence interval. In the LIT- Spondias mombin leaf extract gave an R2 value of 0.73, Sy.x = 13.00 with an EC50 value of 4.0mg/ml at 95 % confidence interval, than cypermethrin (7.40 mg/mL) with an R2 value of 1.0, Sy.x = 0.78 at 95 % confidence interval. In EHT, toxicity to egg hatching was found at 1.25% Triton X-100, as 6% of the eggs hatched to larvae.